Improving Teachers' Capability in Implementing Learning Through Information and Communication Technology (ICT)-based Academic Supervision in the Gugus V Teacher Working Group in Tambang - Ekasiswi, Nur (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
This research aims to improve teachers' abilities in implementing learning through information and communication technology (ICT)-based academic supervision. Professional teachers are those who have mastered four main competencies, including; (1) pedagogical (academic) competencies, (2) personality competence (personal), (3) social competence, and (4) professional competence. These four competencies must always be improved in accordance with current developments. Academic supervision is an activity that creates appropriate conditions for the teacher's continued professional growth. This research is School Action Research in which a research that consists of a series of steps consisting of planning activities, implementing actions, observations, and reflection activities. Based on the results of the analysis and discussion, the conclusion indicates the ability of teachers at Elementary School Cluster V Tambang Kampar to carry out learning, which refers to Permendiknas No. 41 of 2007, can be improved through academic supervision in KKG activities. This can be seen from the average level of teacher ability in cycle I, which was 65.05% as classified as poor. It increased in cycle II to 72.14%, which was classified as poor. And in cycle III, it increased to 86.70%, which was in the good category.